Comment on “Towards deterministic equations for Lévy walks: The fractional material derivative” - Chukbar, Konstantin V.; Zaburdaev, Vasily (Physical Review E, 2003)
The connection of problems considered in the paper by Sokolov and Metzler with stochastic transport in usual space and uniform medium is discussed. © 2003 The American Physical Society.
Created from Fastlane, Scopus look-up